Identification and characterization of total petroleum hydrocarbon-degrading bacteria isolated from inoculum tanks and their potential in bioremediation - Pearlycia ., Brooke (Universiti Malaysia Sarawak (UNIMAS), 2010)
Eleven Total Petroleum Hydrocarbons (TPH)-degrading bacteria were successfully isolated from six inocula obtained from Seria Crude Oil Terminal (SCOT) plant in Brunei Darussalam using selective enrichment technique. All isolates were cultivated in liquid media with crude oil as the sole carbon and energy source. The nucleotide sequences of the 16S rRNA gene of these bacteria were determined. Based on biochemical and molecilar characterization performed, the identities of the bacteria capable of degrading hydrocarbons belong to the genus Bacillus, Brevibacillus, Pseudomonas, Agrobacterioum and Stenotrophomonas. All these isolates were assessed for their resistance against antibiotocs like gentamicin, cephalexin, tetracycline, penicillin, erythromycin and vancomycin by mean of Kirby-Bauer disk diffusion method.